2022
DOI: 10.26434/chemrxiv-2022-pgvsc
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Micro-flow Size-Exclusion Chromatography for enhanced native Mass Spectrometry of proteins and protein complexes

Abstract: Native Size-exclusion chromatography (SEC) employing aqueous mobile phases with volatile salts at neutral pH combined with native mass spectrometry (nMS) is a useful tool for the characterization of proteins in their native state. However, in many cases the conditions needed to realize the hyphenation of SEC with MS require relative high activation energy and therefore hinder the analysis of labile protein complexes. In this work, we are investigating the advantages of narrow SEC columns (1 mm internal diamete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Quite excitingly, a new ChemRxiv manuscript by Gargano et al just came out, they demonstrated that with the aid of an ion‐exchange trap before SEC for preconcentration of the sample and a narrow i.d. SEC column (1 mm, 30 cm), a micro‐flow SEC [≤15 μl/min]) offers great sensitivity for nMS of proteins and protein complexes (Ventouri et al, 2022).…”
Section: Applicationsmentioning
confidence: 99%
“…Quite excitingly, a new ChemRxiv manuscript by Gargano et al just came out, they demonstrated that with the aid of an ion‐exchange trap before SEC for preconcentration of the sample and a narrow i.d. SEC column (1 mm, 30 cm), a micro‐flow SEC [≤15 μl/min]) offers great sensitivity for nMS of proteins and protein complexes (Ventouri et al, 2022).…”
Section: Applicationsmentioning
confidence: 99%
“…3 Native mass spectrometry (nMS) provides critical insights into the structures, functions, and dynamics of proteoforms and protein complexes near physiological conditions. [4][5][6][7] Native MS has been widely employed to study well-purified proteoforms and protein complexes with low complexity through either direct infusion [8][9][10][11][12][13] or coupling with online/offline native separation methods, including size-exclusion chromatography (SEC), [14][15][16][17][18] ion-exchange chromatography (IEX), 19,20 hydrophobic interaction chromatography (HIC), 21,22 and capillary zone electrophoresis (CZE). 23 Native proteomics aims to measure endogenous proteoforms and protein complexes under a near physiological condition on a proteome scale and it requires highly efficient separation techniques for protein complexes prior to nMS.…”
Section: Introductionmentioning
confidence: 99%